A new strain of bacteria isolated from chemically saturated corn rhizosphere under the dominance of the mineral kaolinite - SUKMAWATI SUKMAWATI; IRADHATULLAH RAHIM; HARSANI HARSANI; ASWAR SYAFNUR; YADI ARODHISKARA; AHMAD SELAO; LUKI FATHIA NURUL ANISA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sukmawati, Rahim I, Harsani, Syafnur A, Arodhiskara Y, Selao A, Anisa LFN. 2023. A new strain of bacteria isolated from chemically saturated corn rhizosphere under the dominance of the mineral kaolinite. Biodiversitas 24: 1886-1894. The kaolinite mineral that dominates the cornfield reduces soil fertility and the bacterial community. The discovery of adaptive bacterial strains on kaolinite dominant land is a biological strategy to improve soil fertility because it is part of the root ecosystem. This study aims to obtain adaptive and superior bacteria in producing IAA hormones and fixing nitrogen. The soil analysis method uses X-Ray Diffraction (XRD) and X-Ray Fluorescence (XRF) analysis to characterize clay minerals and soil chemical content. While the bacterial characterization was carried out morphologically and physiologically. After that, followed by the 16S rRNA gene sequence analysis. The type of kaolinite clay mineral dominates the soil samples with a SiO2 content of >40%. A total of 17 bacterial isolates were purified, 12 had round colony shapes, and 5 had irregular shapes dominated by cream color, 11 of which were identified as Gram-positive and 6 Gram-negative bacteria. RJ1T isolates/isolated produced the highest auxin (0.141 mgL-1), while RJ1P isolates/isolated had the highest nitrogen fixation ability (0.975%) and were not pathogenic. The isolates were closely related to the Nocardioides marinisabuli strain RA2816S ribosomal RNA gene (99.57%). Thus, RJ1PI bacterial isolate is an adaptive bacteria that can be formulated as a biological agent to increase maize productivity in the dry land.